Antithrombotic potential of ethanol extract from Gardenia jasminoides leaves planted in Aceh - AZIZAH VONNA; NUZUL HIDAYATI; SURYAWATI SURYAWATI (Universitas Syiah Kuala, 2020)
Therapheutic agents from plants are believed to be effective, sustainable and readily available which stimulate researchers to explore various activities of plants. This study is aimed to investigate the activity of Gardenia jasminoides (G. jasminoidesleaves in enhancing the length of bleeding time and clotting time thus can be optimized to be a potential thrombolytic agent in the future. The animal were classified into 5 groups included 3 treatment groups receiving G. jasminoides leaves (GJL) extract at dose 100, 200, 300 mg/kg BW, 1 positive control receiving aspirin 0.208 mg/20 g and 1 negative control. Mice treated with GJL extract delayed the clot formation with the highest dose showed effects as strong as positive control.